Eco-Friendly and Effective Diatomaceous Earth/Peat (DEP) Microbial Carriers in the Anaerobic Biodegradation of Food Waste Products - Agnieszka A. Pilarska (Energies, 2022)
This article aims to present the results of research on anaerobic digestion (AD) of waste wafers (WF-control) and co-substrate system—waste wafers and cheese (WFC-control), combined with digested sewage sludge. The aim of this study was to assess the physicochemical parameters of the diatomaceous earth/peat (DEP; 3:1) carrier material and to verify its impact on the enzymatic activity and the process performance. The experiment was conducted in a laboratory, in a periodical mode of operation of bioreactors, under mesophilic conditions. The results of analyses of morphological-dispersive, spectroscopic, adsorption, thermal, and microbiological properties confirmed that the tested carrier material can be an excellent option to implement in biotechnological processes, especially in anaerobic digestion. As part of the experiment, the substrates, feedstock, and fermenting slurry were subjected to the analysis for standard process parameters. Monitoring of the course of AD was performed by measuring the values of key parameters for the recognition of the stability of the process: pH, VFA/TA ratio (volatile fatty acids/total alkalinity), the content of NH4+, and dehydrogenase activity, as an indicator of the intensity of respiratory metabolism of microorganisms. No significant signals of destabilization of the AD process were registered. The highest dehydrogenase activity, in the course of the process, was maintained in the WFC + DEP system. The microbial carrier DEP, used for the first time in the anaerobic digestion, had a positive effect on the yield of methane production. As a result, an increase in the volume of produced biogas was obtained for samples fermented with DEP carrier material for WF + DEP by 13.18% to a cumulative methane yield of 411.04 m3 Mg−1 VS, while for WFC + DEP by 12.85% to 473.91 m3 Mg−1 VS.